Determinants and outcomes of strategic orientations : empirical evidence from MultiLevel Marketing (MLM) industry of Malaysia / Leila Radmand and Shamsuddin Mukhtaram - Mukhtaram, Shamsuddin; Radmand, Leila (Faculty of Business Management, 2013)
The purpose of this study is primarily to examine the effects of the top management behaviour on the levels of pre-purchase satisfaction and the service profit chain of MLM companies. The sampling size was 453 independent distributors of 25 MLM companies. This study has provided empirical evidence to the argument that strategic orientations are crucial towards the pre-purchase satisfaction and the service profit chain of MLM companies. In particular, market orientation was found to have significant impacts on pre-purchase satisfaction, internal customer orientation, employee motivation and customer commitment. Additionally, pre-purchase satisfaction was found to have significant relationships with customer commitment.